Pengelolaan Persandian Dalam Menjaga Informasi Rahasia Negara Pada Pemerintah Kabupaten Bungo - Ridwan Ridwan; Mulia Jaya; Rusdi Rusdi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2020)
Encoding is one of the mandatory matters that is not related to basic services. To elaborate regional authority related to coding matters, mapping of coding affairs is carried out in the context of structuring the Provincial / Regency / City Regional Institutional Apparatus in the Field of Encoding according to the direction of Law No. 23 of 2014 concerning Regional Government. With the enactment of Law Number 23 Year 2014 in the Jambi Provincial Government, especially in the Bungo District, realizing harmonization of policies between the center and the regions that synergize with each other and will achieve the goals of Regional Autonomy in the welfare of people's lives. In the Bungo Regency in the coding activity supported by 17 sub-districts within the Regency area, the implementation was not yet optimal. This research uses qualitative research methods, qualitative research has a flexible nature. This research found that the implementation of the duties and functions of the Bungo Regency coding team in maintaining confidential government information in the context of efforts to realize the integrity of the Unitary State of the Republic of Indonesia (NKRI) had not gone well. This is evidenced by the lack of awareness and responsibility of the coding team on the duties and functions of the coding field. Obstacles or obstacles facedby the coding team in carrying out their functions in safeguarding confidential government information in an effort to realize the integrity of the Unitary State of the Republic of Indonesia, including lack of awareness and full support from superiors or officials authorized to carry out coding functions and functions, there is no means from the government in the implementation of duties and functions in the coding field.